Religious Tourism in Greece and Cyprus: Re-Cult and Re-Cult Magnum Projects - Kosmas, Petros C.; Drakonakis, Vassilis; Papavasileiou, Spyridon; Paraskeva, Charalambos; Moullotou, Konstantina; Theocharous, Antonis L.; Andreev, Hristo; Panagopoulou, Maria; Giannoulis, Petros (My University, 2022)
Religious tourism is customarily defined as travel for religious purposes and is considered a form of cultural tourism. Recent market research suggests that the number of religious travellers is steadily growing while emerging trends among travellers are the search for authenticity and the diversification of travel experiences by pursuing unusual ways to explore religion. These trends lie at the heart of Re-Cult and Re-Cult Magnum projects implemented under the cooperation programme Interreg V-A Greece-Cyprus. The projects are dedicated to the digitisation of Cultural Heritage and the development of innovative products for religious travellers that integrate ICTs to augment the travellers’ experience. Specifically, the projects use cutting edge digitisation methods (3D scanning, UAV photography, 4K videography, photogrammetry) to digitise both tangible and intangible cultural heritage assets. The assets and associated metadata are stored in a custom-built resources management system and are subsequently conveyed to a host of solutions that enhance the religious traveller’s experience before, during and after the visit. These include a dedicated website with certified pilot religious routes providing all necessary information for planning a visit, a digital museum website allowing virtual tours and the viewing of select monuments and relics in 3D that functions both as an edutainment and a promotional tool incentivising physical visits; a set of mobile apps that provide additional information and 2D/3D imagery for artefacts and monuments during the visit, in-museum augmented reality guided experiences using cutting edge headsets, and on-site info kiosks and holograms that highlight interesting, unusual or unique elements in religious routes. It is hoped that our efforts will significantly enhance the quality of the religious tourism products in Greece and Cyprus and augment the travellers’ physical visit experience in the upcoming, post-pandemic tourist season.